Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw untuk Peningkatkan Hasil Belajar IPS di Sekolah Dasar - Ari Surono; Tarto Tarto (UM Purwokerto Press, 2022)
Social Sciences (IPS) is one of the subject matter contained in the thematic learning of the elementary school curriculum. Social studies learning does not only require the achievement of knowledge competence as indicated by the achievement of the Minimum Completeness Criteria (KKM), but also applicable knowledge that is useful in the environment. Social studies learning in elementary school is one of the lessons that is not popular because of the breadth of material consisting of geography, history and economics. This makes social studies learning outcomes low. The success of learning is influenced by internal and external factors. The use of innovative, fun and meaningful learning media is one of the causes of external factors. In this problem, teachers are required to be able to use various media, models and learning methods that can attract students to learn. One of the innovative learning models is the Jigsaw model. The formulation of the problem in this study is whether the application of the Jigsaw type cooperative learning model can improve social studies learning outcomes. This research was conducted in two cycles. Each cycle consists of four stages, namely planning, action, observation, and reflection. The method of collecting data is through tests, observing student learning activities, and teacher performance during learning. Indicators of the success of this research are the average value of student learning outcomes is equal to 72, with a minimum mastery percentage of 75%, student activity in learning activities of at least 75%, and teacher performance score of at least B (71). The results showed that in the first cycle the average value of student learning outcomes was 73.95 with classical learning completeness 73.69%, student activity in the learning process was 74.60% with high criteria, and teacher performance scores were 85.21 ( A). In cycle II the average value of student learning outcomes is 81.84 with classical learning completeness 78.95%, student activity in the learning process is 81.47% with very high criteria, and teacher performance value is 92.86 (A). These results indicate an increase from cycle I to cycle II. Based on the results obtained, it can be concluded that the Jigsaw cooperative learning model is proven to improve student learning outcomes and activities, as well as teacher performance.